Zoe LeDonne: capstone - LeDonne, Zoe, artist (Colorado State University. Libraries, 2015)
The artist's statement: The work presented in my capstone centers around the theme of being overwhelmed. I have examined the different facets of this feeling and how it has manifested itself in my own experiences. I wanted to explore what being overwhelmed meant for myself, and in the process touch on a range of shared experiences many of us have had. Being overwhelmed is a common experience to everyone, especially to students, and is an emotion that has multiple facets that can be explored. Although the work is grounded within personal experience and reference, I did not want my image to predominate in the pieces. To create a more generalized view of the figure in the pieces, I obscured the figure in various ways to eliminate personal identity. In this way, I hope for the viewer to feel like they can connect the imagery in the pieces with their own personal experiences. All of the pieces draw on the use of plants and animals as metaphors for different aspects of being overwhelmed. Nettles, English ivy, and hemlock are all either poisonous or invasive. Ticks, cicadas, and mice are generally viewed as nuisances for various reasons. Using plants and animals as metaphors allows me to stray from displaying more obvious representations of being overwhelmed within the figures in the paintings.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.